Ceramaster patagonicus Sladen 1889 - Mah, Christopher L. (Zenodo, 2011)
Ceramaster patagonicus (Sladen, 1889) (Figure 2 A–G) Sladen, 1889: 269, pl. 46, figs 3–4, pl. 44, figs 3–4. (as Pentagonaster patagonicus ) Perrier, 1891: K127, pl. 12, figs 3a–b (as Pentagonaster austrogranularis ) Verrill, 1899: 195 (as Mediaster patagonicus ) Verrill, 1899: 195 (as Pseudarchaster patagonicus ) Fisher, 1911: 214, pl. 37, fig. 4,, pl. 38, figs 1–2, pl. 40, fig. 3; 1940: 118; Djakonov, 1950: 48, figs. 27, 48; Bernasconi, 1963: 8, pl. 1, figs. 1–2, pl.2, fig. 3; Baranova & Belyaev 1968: pl. 17, fig. 2; Tommasi, 1970: 12, fig. 36; Lambert, 1978: 62; Anderson et al. , 1993: 502; Branch et al. , 1993: 44 (illustr.); A.M. Clark, 1993: 249; Rowe & Gates, 1995: 65; O’Hara, 1998: 179, pl. 1d.; H.E.S. Clark in Clark & McKnight, 2001: 33; Stampanato & Jangoux, 2004: 4, 6 (as Ceramaster patagonicus ) McKnight, 1973: 178, fig. 4; 1984: 142; A.M. Clark, 1993: 249 (as Ceramaster lennoxkingi ) Clark & Downey, 1992: 236 (as Ceramaster grenadensis patagonicus ) Range. Broadly distributed. Bering Sea, Aleutian Islands, Alaska to British Columbia, Gulf of California to southern Australia (North of Macquarie Island), New Zealand and outlying areas (Bounty Islands and Macquarie Island). South Atlantic from near Cape Horn, Straits of Magellan, Falkland Islands, Falkland Plateau, Burdwood Bank. South Indian Ocean: Crozet Island, Kerguelen, Marion and Prince Edwards. 18–1125 m. Material examined. Strait of Magellan. USNM E13497 East of Cape Froward, Strait of Magellan, Chile. 53°56’S, 71° 15’W, 256– 320 m. Coll. R/V Eltanin , USARP, 6 Feb 1964. (1 dry spec. R=5, r=3.3). USNM 1081976 Desolacion Island, Strait of Magellan. 52°53’S, 74° 05’W to 52°50’S, 74°10’W, 522– 544 m. Coll. R/V Eltanin , USARP, 1 April 1966. (2 dry specs. R=5.2, r=2.8; R=4.4, r=2.6); USNM 1082906 Strait of Magellan, west mouth, 52°41’S, 74°35’W, to 52°45’ S, 74°28’W, 188– 247 m. Coll. R/V Eltanin , USARP, 6 Jan 1966 (1 dry spec. R=4.4, r=2.9); USNM 112246 Cape Froward, Strait of Magellan, Chile. 53°38’48S, 70° 55’ 06W, 101– 119 ...